Development of Intertextual-Based E-Book on the Concept of Buffer Solution - Nur Sehasari Dewi (Jurnal Tadris Kimiya, 2022)
Students are necessary to understand macroscopic, sub-microscopic, and symbolic representations levels in buffer solution concept. The research aims to develop the intertextual-based e-book on the concept of buffer solution. The study is part of the research and development plan for creating teaching materials. Stages of research are conducted as follows research and information collecting, planning, and developing the preliminary form of product. Based on the result, the product of teaching material has characteristic, which is connecting the three levels of chemical representation on the buffer solution concept. Due to their visualization character and multiple representational relationship, interactive e-books demonstrate the power and value of modeling, learning, and assessment perspectives. Intertextual e-books potential to be implemented as teaching materials in buffer solution concepts.